1988
DOI: 10.1227/00006123-198803000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Hearing after Removal of Cerebellopontine Angle Meningioma: Diagnostic and Therapeutic Implications

Abstract: A case of cerebellopontine angle meningioma with restoration of hearing from a profoundly deaf state is presented. Meningiomas of the posterior fossa commonly present with decreased or absent hearing and can appear deceptively similar to acoustic neurinomas on radiographic and audiometric testing. Because total restoration of hearing can occur with meningioma, even with significant preoperative deficit, utilization of the translabyrinthine approach is less desirable if any preoperative question as to the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…In one deaf patient with a retromeatal tumor (Group 5), even dramatic hearing recovery to normal hearing was observed. Few case reports have previously demonstrated that hearing restoration can occur with CPA meningiomas, even in the face of profound preoperative deficit (4,7,18,35). In our view, these cases show that it is worth attempting hearing preservation in as many patients as possible, even in the case of bad or no clinical preoperative hearing.…”
Section: Discussionmentioning
confidence: 60%
“…In one deaf patient with a retromeatal tumor (Group 5), even dramatic hearing recovery to normal hearing was observed. Few case reports have previously demonstrated that hearing restoration can occur with CPA meningiomas, even in the face of profound preoperative deficit (4,7,18,35). In our view, these cases show that it is worth attempting hearing preservation in as many patients as possible, even in the case of bad or no clinical preoperative hearing.…”
Section: Discussionmentioning
confidence: 60%
“…1,2,4,6,8,9) This dramatic recovery seems to occur more commonly in`non-acoustic' tumors than in acoustic neuromas. 8) When a tumor is located in a cistern other than the cerebellopontine cistern, the 8th cranial nerve together with its feeder from the internal auditory artery are separated from the tumor by the arachnoid membrane between the two cisterns.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, hearing restoration may paradoxically occur in patients with relatively large tumors. 6,8,9) Small tumors with hearing loss, which are usually acoustic tumors, are more likely to impair 8th cranial nerve function directly and radically. Preoperatively, the auditory brainstem response 9) or otoacoustic emissions, 1) which is assumed to be generated by the outer hair cells of the cochlea, may be useful for detecting patients in whom hearing loss is potentially reversible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations